An irrigation controller mechanically actuated by soil-water tension: I - Design, development and laboratory evaluations - Alexsandro C. S. Almeida; Tarlei A. Botrel; Steven R. Raine; Antonio P. de Camargo; Marinaldo F. Pinto; Conan A. Salvador (Revista Brasileira de Engenharia Agrícola e Ambiental)
ABSTRACT The objective of this study was to develop and evaluate an irrigation controller that was mechanically actuated by soil-water tension within laboratory conditions. The controller was designed and constructed using readily available hydraulic fittings and other componentry. The main components of the controller were a tensiometer; a rubber diaphragm that moves according to the variation in tension inside of the tensiometer; an activation rod that transfers the movement from diaphragm to the switch valve; and a steel spring that regulates the activation of soil water tension. Six irrigation controller samples were tested in the laboratory to evaluate the mechanical performance and component forces required to activate the controllers. The relationship between spring adjustment and soil water tension required to open the irrigation valve was linear with a gradient ranging from 1.10 to 1.41 kPa mm-1 and a coefficient of variation of 9.2%. However, differences observed in the activation of the soil water tension could also be reduced by individual controller calibration. The calibration of the soil water tension required to initiate irrigation was easily set by adjusting the spring. The proposed controller is functional, simple to use, can be easily adjusted, and does not require electricity to operate.